Influence of Exogenous Substrates on the Endogenous Respiration of Pseudomonas aeruginosa - Gronlund, Audrey F. (1966)
Gronlund, Audrey F. (University of British Columbia, Vancouver, Canada), and J. J. R. Campbell. Influence of exogenous substrates on the endogenous respiration of Pseudomonas aeruginosa. J. Bacteriol. 91:1577–1581. 1966.—The influence of growth conditions, ammonium ions, and glucose concentration on endogenous respiration in Pseudomonas aeruginosa was determined by measuring C(14)O(2) evolution from uniformly labeled cells that had previously been grown on C(14)-glucose. A 93% suppression of endogenous C(14)O(2) evolution was evident under growth conditions, and a 66% suppression was observed in the presence of excess glucose. Increasing exogenous glucose concentrations supported decreasing levels of endogenous C(14)O(2) evolution. Ammonium ions slightly suppressed endogenous activity and enhanced the decrease in C(14)O(2) release observed with exogenous glucose. In addition, the effect of exogenous glucose, α-ketoglutarate, 2-ketogluconate, aspartic acid, and adenosine selectively on both endogenous ribonucleic acid (RNA) and protein oxidation was followed by measuring C(14)O(2) evolution from cells grown with C(14)-uracil or C(14)-proline. The five exogenous substrates examined suppressed endogenous RNA oxidation, and the degree of suppression appeared to be correlated with the amount of oxygen consumption and, hence, energy gained during the oxidation of these substrates. Oxidation of endogenous protein was decreased when cells were incubated with glucose, aspartate, and adenosine, but was increased when α-ketoglutarate and 2-ketogluconate were the exogenous substrates. The influence of the oxidizable exogenous compounds appeared to be related, in part, to the ammonium ion requirement imposed upon the cells for assimilation of the individual exogenous substrate.